1999
DOI: 10.1089/10430349950016357
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin-Liposome-Mediated Systemic p53 Gene Therapy in Combination with Radiation Results in Regression of Human Head and Neck Cancer Xenografts

Abstract: The use of cationic liposomes as nonviral vehicles for the delivery of therapeutic molecules is becoming increasingly prevalent in the field of gene therapy. We have previously demonstrated that the use of the transferrin ligand (Tf) to target a cationic liposom e delivery system resulted in a significant increase in the transfection efficiency of the complex [Xu, L., Pirollo, K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
178
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(184 citation statements)
references
References 25 publications
6
178
0
Order By: Relevance
“…26 Indeed, we have shown that the restoration of p53 function via SGT-53, a tumor-targeted nanomedicine, could inhibit tumor growth and sensitize xenografts of human tumors in nude mice lacking T cells to both chemotherapy 27,28 and radiotherapy. 29 Nonetheless, it has become clear that p53 also participates in various aspects of immune modulation in cancer. 30 In the present study, we are reporting that introducing functional wtp53 gene via SGT-53 can induce immunogenic changes of cancer cells, effectively promote anti-tumor immunity, and reduce tumor-induced immunosuppression in the TME.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Indeed, we have shown that the restoration of p53 function via SGT-53, a tumor-targeted nanomedicine, could inhibit tumor growth and sensitize xenografts of human tumors in nude mice lacking T cells to both chemotherapy 27,28 and radiotherapy. 29 Nonetheless, it has become clear that p53 also participates in various aspects of immune modulation in cancer. 30 In the present study, we are reporting that introducing functional wtp53 gene via SGT-53 can induce immunogenic changes of cancer cells, effectively promote anti-tumor immunity, and reduce tumor-induced immunosuppression in the TME.…”
Section: Discussionmentioning
confidence: 99%
“…The p53 expression plasmid pCMV-p53 contains the 1.7 kb human wtp53 cDNA under the control of the CMV promoter, followed by the SV40 polyadenylation signal. 29 As a control treatment, scL-GFP or scL-vec nanocomplexes were prepared using either GFP expression plasmid pCMV-GFP or empty plasmid pCMV, respectively. After incubation for 4 h at 37°C, the medium was replaced with complete medium and the cells were further incubated.…”
Section: Methodsmentioning
confidence: 99%
“…Transferrin has also been used to target plasmids for tumor delivery. 18,[36][37][38] In order to identify a suitable cell line for preparing a mouse xenograft tumor model, the relative levels of transferrin uptake in three human carcinoma cell lines (A2780, HT-29 and HeLa) was determined (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, transferrin incorporated into liposomes can substantially enhance efficiency of gene transfer mediated by the liposome. 29,30 Several groups, including our own, have used recombinant antibody fragments (Fab and ScFv ) as ligands in the design of targeted nonviral gene transfer vectors. 13,14,19 The bifunctional nonviral vector we previously reported is of human origin, but difficulty in large -scale isolation of the Fab protamine fusion proteins was felt to restrict its further development.…”
Section: Discussionmentioning
confidence: 99%